The Effectiveness Of Group Counseling With A Solution-Focused Brief Counseling Approach To Promote Students' Career Maturity - Aisyah, Siti; Sugiyo, Sugiyo; Saraswati, Sinta (Jurnal Bimbingan Konseling, 2023)
Career maturity is a prominent part of a student’s life and career selection. This study aimed to determine the effectiveness of group counseling with a solution-focused brief approach to promote the career maturity of second grade students at SMK Teuku Umar Semarang. It was a quasi-experiment and used a non-equivalent control group design by employing two groups, namely control and experimental groups. In terms of sample, 16 students with low career maturity were chosen from 180 population of second grade students at SMK Teuku Umar Semarang. Following the Wilcoxon Signed Rank and Mann-Whitney Tests, the group counseling with a solution-focused brief approach has been effective to promote the career maturity of the students at SMK Teuku Umar Semarang. For more, the findings, implications and limitations are further in the discussion section of this paper.